Research beyond Randomised Controlled Trial: The Importance of Pragmatic Clinical Trials for Generating Real-world Evidence in Current Healthcare - Sangita Jogdand; Smruti Besekar; Satyawan Singh Patel (Journal of Clinical and Diagnostic Research)
The potential of Real-world Evidence (RWE) to provide valuable insights from Real-world Data (RWD) has drawn a lot of attention recently. This shift focuses research from controlled conditions to real-world, everyday healthcare settings. The shortcomings of conventional Randomised Controlled Trials (RCTs) and Experimental Controlled Trials (ECTs) have led to the emergence of Pragmatic Clinical Trials (PCTs), which emphasise real-world, everyday healthcare settings. The various studies argues that PCTs can bridge the gap between efficacy and practical application in clinical research by incorporating diverse patient groups, adaptable procedures and outcome measures relevant to daily clinical practice. Therefore, this current study highlights the potential of PCTs to connect RCTs and clinical practice by examining the concept of RWE and the tests’ distinguishing features.